2023
DOI: 10.1002/jsp2.1240
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic loading leads to increased metabolic activity and spatial redistribution of viable cell density in nucleus pulposus tissue

Abstract: Background Nucleus pulposus (NP) cell density is orchestrated by an interplay between nutrient supply and metabolite accumulation. Physiological loading is essential for tissue homeostasis. However, dynamic loading is also believed to increase metabolic activity and could thereby interfere with cell density regulation and regenerative strategies. The aim of this study was to determine whether dynamic loading could reduce the NP cell density by interacting with its energy metabolism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
(198 reference statements)
0
4
0
Order By: Relevance
“…proposed that dynamic loading acts as an additional stressor, leading to a decrease in nucleus pulposus (NP) cell density. 33 and high (0.1-1.2 MPa). They observed that cell viability remained above 80% at low and medium loads, while both nucleus pulposus (NP) and annulus fibrosus (AF) cell viability were impacted by high loads.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…proposed that dynamic loading acts as an additional stressor, leading to a decrease in nucleus pulposus (NP) cell density. 33 and high (0.1-1.2 MPa). They observed that cell viability remained above 80% at low and medium loads, while both nucleus pulposus (NP) and annulus fibrosus (AF) cell viability were impacted by high loads.…”
Section: Discussionmentioning
confidence: 96%
“…13,31,32 Salzer et al observed an increase in the metabolic activity of NP tissue with dynamic loading, coupled with a notable reduction in living cell density by the seventh day. 33 Kurakawa et al reported diminished cell density and viability in nucleus pulposus cells subjected to dynamic compression loading of rat intervertebral discs at 1.5 Hz. 34 collagen in loading conditions involving 1.3 MPa, 5.0 Hz, and 8 h. 35 Cui identified new epitope peptides formed by proteoglycan and collagen cleavage during IVD degeneration in one strike model, serving as promising biomarkers of early disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations